2013
DOI: 10.1051/0004-6361/201321220
|View full text |Cite
|
Sign up to set email alerts
|

Protoplanetary disk evolution and stellar parameters of T Tauri binaries in Chamaeleon I

Abstract: Aims. This study aims to determine the impact of stellar binary companions on the lifetime and evolution of circumstellar disks in the Chamaeleon I (Cha I) star-forming region by measuring the frequency and strength of accretion and circumstellar dust signatures around the individual components of T Tauri binary stars. Methods. We used high-angular resolution adaptive optics JHK s L -band photometry and 1.5-2.5 μm spectroscopy of 19 visual binary and 7 triple stars in Cha I -including one newly discovered tert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(95 citation statements)
references
References 68 publications
7
88
0
Order By: Relevance
“…The A V = 3.4 mag derived here is smaller than the A V > 4 mag reported by Daemgen et al (2013), while the L determined here is the same as that reported by Daemgen et al (2013) for component B. It is thus possible that in the VIS and UVB arm the spectrum of component B dominates, as Daemgen et al (2013) reported that component A has A V = 10.5 mag and it is as bright as component B in the near-infrared. The latter has only A V = 4.3 mag, according to Daemgen et al (2013), thus at optical wavelengths component B is significantly brighter than component A.…”
Section: B1 Chamaeleon I Targetssupporting
confidence: 57%
See 3 more Smart Citations
“…The A V = 3.4 mag derived here is smaller than the A V > 4 mag reported by Daemgen et al (2013), while the L determined here is the same as that reported by Daemgen et al (2013) for component B. It is thus possible that in the VIS and UVB arm the spectrum of component B dominates, as Daemgen et al (2013) reported that component A has A V = 10.5 mag and it is as bright as component B in the near-infrared. The latter has only A V = 4.3 mag, according to Daemgen et al (2013), thus at optical wavelengths component B is significantly brighter than component A.…”
Section: B1 Chamaeleon I Targetssupporting
confidence: 57%
“…The stellar parameters (SpT, A V , L ) for all the targets discussed here have previously been derived by several studies (e.g., Luhman 2007;Spezzi et al 2008;Daemgen et al 2013;Frasca et al 2015, cf. Tables A.1-A.2).…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Daemgen et al (2013) have investigated the impact of binary companions on the evolution of circumstellar disks and concluded that they evolve faster in binary systems. In this context, we decided to remove the binaries (and multiple systems) from our sample to inspect this point.…”
Section: T Tauri Disk Lifetimes In the Lupus Associationmentioning
confidence: 99%